E-Government Development: Catalysing Agile Governance Transformation in Indonesia - Dyah Mutiarin; Nur Khaerah; Andi Visca Irfa Nyssa; Nasrulhaq Nasrulhaq (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
E-government is considered a crucial instrument for service transformation as it is believed to assist in achieving the government’s objectives by functioning as a flexible digital service platform for development. Nevertheless, our understanding of its potential impact on governance remains limited, particularly regarding the advancements made in digital-based services for the public sector inside government and the resulting level of public satisfaction. This study examines the crucial significance of e-government in the restructuring of agile governance in Indonesia. Qualitative research methods are employed for this research. Data related to the E-Government Development Index (EGDI) are collected through the United Nations website. After successfully retrieving the data and presenting it in a suitable format, the authors analysed Indonesia’s overall EGDI score and examined individual EGDI indicator levels. The findings show that the Indonesian government has accelerated the implementation of e-government, catalysing the digitalisation of governance and improving efficiency, transparency and public engagement. The report asserts that e-government can revolutionise governance in Indonesia, rendering it more agile and responsive. Nevertheless, a requirement remains to enhance and augment the e-government infrastructure and implement policies that foster digital inclusivity to bolster Indonesia’s governance capabilities. By bolstering e-governance, the government will enhance its efficacy in addressing forthcoming crises and augment citizen participation in policy formulation.